Pengaruh Harga, Promosi, Dan Lokasi Terhadap Kepuasan Pelanggan Café Bukan Main Coffee - Reiki Vega Diondah; Nurhajati Nurhajati; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect price, promotion, and location over customer satisfaction. The population in this study are Café Bukan Main Coffee. The data collection method in this study used a questionnaire with a sample of 90 respondents. The independent variable in this study is the price, promotion, and location and the dependent variable is the customer satisfaction. The analytical method used in this study is multiple linear regression analysis and processed using SPSS 26. The results of this study simultaneously show that the price, promotion, and location has a positive effect and significance on customer satisfaction. Partially, price, promotion, and location have a positive effect and significance on customer satisfaction. Keywords: Financial Literacy Financial Education In The Family, Self-Control And Financial Management.